Optimal location and sizing of real power DG units to improve the voltage stability in the distribution system using ABC algorithm united with chaos. (March 2015) - Mohandas, N.; Balamurugan, R.; Lakshminarasimman, L.
Highlights: Artificial Bee Colony (ABC) algorithm is combined with chaos theory. Different impact indices are considered in the problem formulation. Different load models such as residential, industrial, commercial are considered. Three real power DGs are considered in the proposed approach. Abstract: The introduction of a Distributed Generation (DG) unit in the distribution system improves the voltage profile and reduces the system losses. Optimal placement and sizing of DG units play a major role in reducing system losses and in improving voltage profile and voltage stability. This paper presents in determination of optimal location and sizing of DG units using multi objective performance index (MOPI) for enhancing the voltage stability of the radial distribution system. The different technical issues are combined using weighting coefficients and solved under various operating constraints using a Chaotic Artificial Bee Colony (CABC) algorithm. In this paper, real power DG units and constant power load model and other voltage dependent load models such as industrial, residential, and commercial are considered. The effectiveness of the proposed algorithm is validated by testing it on a 38-node and 69-node radial distribution system.